The Influence of Project-Based Learning on Grade XI Students Achievement in Electrical Installation at SMK Negeri 5 Makassar - Ashari, Hilda; Iswal Burhan, Muhammad; Arjund Arnold, Muh (Jurnal Pendidikan dan Profesi Keguruan, 2025)
​This study examines the influence of the Project-Based Learning (PjBL) model on students’ learning achievement in an Electrical Lighting Installation subject at SMK Negeri 5 Makassar. The urgency of this research arises from the persistent gap between theoretical understanding and practical application in vocational education, where teacher-centered instruction often limits engagement and problem-solving skills. Using a quasi-experimental design with a non-equivalent control group, the 33 Grade XI students were divided into an experimental class (n=16) and a control class (n=17). Data were collected through pre-tests, post-tests, and questionnaires and analyzed using a t-test with SPSS 26. The results showed that the average post-test score in the experimental group increased from 30.19 to 83.69, while that in the control group improved from 25.18 to 69.24, with a significance value of 0.001 (<0.05), indicating that PjBL had a significant positive effect on learning outcomes. Students also responded positively to PjBL implementation (average 86%), indicating increased motivation and collaboration. These findings confirm that PjBL effectively enhanced cognitive understanding and learning engagement in vocational education. However, this study was limited by its small sample size, short intervention period, and focus on cognitive aspects only. Future studies should adopt larger samples, extended durations, and mixed-method approaches to assess the long-term impacts on psychomotor and affective competencies.​